Pedagogical-Psychological Possibilities of Professional-Methodological Training of the Future Teacher of Fine Arts - Bekmuratova Shakhida Ne’matjonovna (Global Scientific Publishing, 2023)
This article covers the current issue, the pedagogical and psychological possibilities of professional and methodical training of the future art teacher.
Keywords: perspective; color science; optics and light and shadow laws; anatomy